PERAN RELIGIUSITAS DAN PERSEPSI RISIKO DALAM PENGAMBILAN KEPUTUSAN ANGGOTA BMT : SEBUAH STUDI LITERATUR - Abdul Hamid; Muh Syarif; Suyono (Universitas Sarjanawiyata Tamansiswa, 2026)
The growth of the Islamic microfinance sector in Indonesia through Baitul Maal wat Tamwil (BMT) faces significant challenges regarding the escalation of risk perception and institutional stability, which potentially erode public trust. This study aims to analyze the strategic role of religiosity in mitigating the influence of risk perception on the decision to become a BMT member. Utilizing the Systematic Literature Review (SLR) method, this research evaluates reputable literature from the last five years to map the interaction between psychological variables and spiritual dimensions. The results indicate that religiosity is a crucial determinant, functioning as a normative filter and an effective moderating variable in reducing member anxiety toward both operational and financial risks. The main findings reveal that members with high levels of religiosity tend to prioritize transcendental dimensions and the pursuit of barakah (blessings), thereby maintaining loyalty through the internalization of Sharia values, which are perceived as a guarantee of moral security. Economic decisions in this context are not merely mathematical calculations but a form of faith integrity. Practical implications of this study suggest that BMT managers adopt a hybrid strategy that combines spiritual security narratives with accountable technical governance transparency to strengthen their competitive position in the contemporary market. The integration of technical efficacy and spiritual conviction is the primary key to maintaining customer base stability amidst the volatility of the modern financial industry.